Auto-consistent test of Galaxy star formation histories derived from resolved stellar population and integral spectroscopy - Rodrigues, M; Patricio, V; Rothberg, B; Sanchez-Janssen, R; Vale Asari, N (Astronomical Society of India, 2013)
We present the first results of our observational project ’Starfish’ (STellar Population From Integrated Spectrum). The goal of this project is to calibrate, for the first time, the properties of stellar populations derived from integrated spectra with the same properties derived from direct imaging of stellar populations in the same set of galaxies. These properties include the star-formation history (SFH), stellar mass, age, and metallicity. To date, such calibrations have been demonstrated only in star clusters, globular clusters with single stellar populations, not in complex and composite objects such as galaxies. We are currently constructing a library of integrated spectra obtained from a sample of 38 nearby dwarf galaxies obtained with GEMINI/GMOS-N&S; (25h) and VLT/VIMOS-IFU (43h). These are to be compared with color magnitude diagrams (CMDs) of the same galaxies constructed from archival HST imaging sensitive to at least 1.5 magnitudes below the tip of the red giant branch. From this comparison we will assess the systematics and uncertainties from integrated spectral techniques. The spectra library will be made publicly available to the community via a dedicated web-page and Vizier database. This dataset will provide a unique benchmark for testing fitting procedures and stellar population models for both nearby and distant galaxies.